The Relationship Between Short- and Long-Term Foreign Loans Obtained by the Private Sector and the Stock Market in Turkey: An Empirical Analysis on the BIST 100 Index (Third Sector Social Economic Review, 2026)
In this study, the effects of the external borrowing structure of the private sector and domestic financing sources on the stock market in Türkiye are analyzed using the ARDL (Autoregressive Distributed Lag) method for the period 2010:M1 – 2024:M12. In this context, the relationship between the BIST 100 index and the private sector's short-term and long-term debts obtained from abroad, total loans provided by banks, and three-month deposit interest rates has been examined. The ARDL approach allows for the separate investigation of both short- and long-term relationships among the variables, while structural breaks are accounted for through a dummy variable incorporated into the model. The empirical findings reveal that the BIST 100 index is sensitive to changes in short-term external borrowing and interest rates. In the long run, short-term external borrowing exerts a positive and statistically significant effect on the index, whereas interest rates have a significant negative impact. The influence of domestic credit volume is weak and negatively signed. Although long-term external debt carries a negative coefficient, it is not statistically significant. In the short run, the error correction term is found to be negative and significant, indicating the model's convergence toward long-term equilibrium. Short-term external debt continues to exert a positive influence during this period, while interest rates again display a negative effect. The negative and statistically significant coefficient of the dummy variable used in the analysis indicates that the exchange rate crisis, the COVID-19 pandemic, and global uncertainties during this period exerted a negative impact on stock market performance. These findings offer important strategic insights for policymakers.
Keywords: BİST 100 Index; Short-Term Foreign Loans; Long-Term Foreign Loans; Private Sector Loans; Deposit Interest Rates; Capital Markets